On the Sale and Purchase of Agricultural Land by Young People in Light of the Main Rules of Land Acquisition in Hungarian Law - Reti, Maria (European Scientific Journal, ESJ, 2026)
The object of this study is to present the main rules on the acquisition of agricultural land by young people in Hungarian agrarian law. It aims to highlight the importance of the younger generation in agriculture and to present examples within Hungary’s land acquisition rules that support young people. Accordingly, it highlights the regulatory approach of the Hungarian legislator, which includes special rules for young people with preferences set apart from the general land acquisition rules. The analysis focuses on the basic law of Hungarian agricultural law on land transactions, which was enacted in 2013 (Land Transaction Act). Based on this legislation, the study examines in detail the relevant concepts, categories, and areas of law. In this context, the analysis of the concept of young farmers is particularly noteworthy, as it is based on the definition developed within the regulatory regime of the European Union’s common agricultural policy and builds on the concept of farmers established under Hungarian agricultural law. The study aims to show that Hungarian agricultural legislators intend to promote generational change and sustainable Hungarian agriculture by introducing regulations that favour young people seeking to acquire land. Among the concepts, the study gives special attention to agricultural land, exploring its multifunctional character, and provides a detailed analysis of, for example, the institution of pre-emptive rights, which are also beneficial for young farmers. From a methodological perspective, the legal-dogmatic and comparative law methods are predominant, particularly in demonstrating the interrelations between specific legislative provisions. The analysis adapts individual sources of literature and legislation to this methodology, as well as relevant information and data. The key finding of the analysis is that the Hungarian legislator has enacted several specific provisions to support young people and to promote generational renewal in agriculture.